Human Security, Consumer Confidence, and the Future of Neoliberalism - Jonathan Nitzan (The Bichler and Nitzan Archives, 2001)
The two opening shots have been fired. On September 11, 2001, someone orchestrated an unprecedented suicide attack on the World Trade Centre in New York and on the Pentagon in Washington DC. The U.S. government immediately laid the blame on Osama bin Laden and his al Qaeda organization. It announced a total `war on terrorism,' imaginatively nicknamed `infinite justice,' and quickly moved to retaliate. On October 7, together with British forces and the blessing of many countries, it launched its first retaliation, bombing targets in Afghanistan, where bin Laden allegedly hides. Much has already been written on the background and causes of these developments, and no doubt more will be coming. But so far, there has been little attempt to understand the possible consequences for contemporary capitalism. There is a real likelihood that these two events will mark the beginning of a global cycle of violence, with military operations, terror attacks, retaliations and counter-retaliations becoming the hallmark of the new century. And yet, could this type of warfare coexist with neoliberal capitalism? Can the ideology of `consumer sovereignty' survive the reality of human insecurity? How might the new reality of terror affect the accumulation of capital? Will it engender a conflict within the ruling capitalist class? And if so, could such conflict open alternative possibilities for a less violent future?
Keywords: 330; consumer confidence; consumption; human security; investor confidence; military spending; neoliberalism; profit; terrorism; tourism; war